Some Surprising Transformations of Colchicone and Other Colchicine‐Derived Tropolones. Issue 46 (4th October 2021) - Stein, Andreas; Hilken née Thomopoulou, Persefoni; Schulte, Tim; Neudörfl, Jörg; Breugst, Martin; Schmalz, Hans‐Günther
Abstract: The alkaloid colchicine represents a prominent lead structure for the development of tubulin‐binding chemotherapeutics. In the course of explorative research into semi‐synthetic colchicinoids we stumbled upon a number of unexpected and mechanistically surprising transformations which reflect the very particular reactivity of the tropolone ether unit and its interplay with adjacent functional groups. Examples are the selective C‐8‐methylation of colchicone upon reaction with the Wittig reagent triphenylphosphonium methylide, the AlMe3 ‐mediated isomerization of colchicone to a tetracyclic lactone, and the cyanide‐induced reaction of the colchicol‐derived mesylate to a rearranged and ring B‐defunctionalized cyano‐allo‐colchicinoid. Finally, the fragmenting rearrangement of a tetracyclic colchicinoid with BF3 ⋅OEt2 in the presence of vinyl‐MgBr afforded a tropolonyl difluoroborate under concomitant transfer of an O‐methyl group from ring C to ring A. Abstract : Who would have predicted the reactions outcome? Derivatives of the prominent alkaloid colchicine were found to react in a very surprising fashion with common reagents to afford unexpected products. The unique reactivity of tropolone ethers and their subtle interplay with adjacent functional groups have to be taken into account to solve the mechanistic puzzles.